Fuel briquettes from crop waste - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1996)
A project to evaluate the technical and material potential of fuel briquetting technology in Zimbabwe was successfullycompleted between 1992 and 1994. Its objective was to use crop-wastes to produce fuel briquettes that can partly substitutethe...